O design estratégico como catalisador do desenvolvimento da arquitetura organizacional de laboratórios de inovação social - Ribeiro, Rafael Vinicius (Universidade do Vale do Rio dos Sinos, 2016)
Society’s ability to adapt it self to the constant changes that comes through is linked to its ability to innovate. Innovate in products, services, means of production and socially. Based on the notion that innovation is essential for this process of adaptation, it is proposed that the strategic design occupies a prominent position in the construction of such initiatives. Among these initiatives can be mentioned social innovation laboratories, which are meant to be a space to reflect on the subject and, above all, where it is practiced. In these laboratories, integrating different actors of society - like people, organizations, universities and the government - it is necessary to develop relationships that allow working together. Relationships that go beyond the formal labor contracts. Relationships that can not always be described, but, however, influence how all these actors work together. To these relations we call relational contracts and organizations that are able to develop them eventually get generate competitive advantage through the strategic lever of organizational architecture. Thus, this research aims to discuss how the strategic design, through its ability to trigger dialogue between the actors of an ecosystem can contribute to the development of architecture as a strategic lever for social innovation laboratories from the study of case of Mercur innovation lab, located in Santa Cruz do Sul, Rio Grande do Sul. As a result, shows the description of the laboratory and the interactions in it and through it occur. Analyzes the typology and it is proposed that they should not be classified, but to develop its own combination of features that may not necessarily fit in a standard operation. Finally present the capabilities of strategic design identified in this research as contributor to the development of organizational architecture as a strategic lever for social innovation laboratories. They are the ability to articulate different points of view, to map resources and actors needed for a project and make visual ideas and thoughts.
Keywords: Design estratégico; Laboratórios sociais; Inovação social; Arquitetura organizacional; Propósito; Strategic design; Social laboratories; Social innovation; Organizational architecture; Purpose; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial